Analysis of Metric Sexing Determination of Dry Hip Bones in Eastern Nepalese People: Analysis of Metric Sexing Determination of Dry Hip Bones in Eastern Nepalese People - Mallick, Dr. Ram Lala (International Journal of Pharmaceutical & Biological Archive, 2018)
Skeletal characteristics differ among individuals. Each population, therefore, possesses specific standards to optimize their identification accuracy. As certain features (e.g., bones of human body and enamel of tooth and skeletal) remain intact after death, these provide the precious tools for sexing of individuals in either the field of medicine or related to prehistoric osteological collections. As the sex hormones influence different reproductive function, the size-related sexual variations exist in nature remarkably. In contrast, the hip bone is an ideal bone to use for sex determination. In spite of their critical use, the findings for the determination of metric sexing with utilization of hip bones in Nepalese people still remain unknown. We, therefore, collected human hip bones and carried out the study to determination of metric sexing. Interestingly, our findings have made the present study of interest from anatomical, anthropological, and forensic points of views.